Blunt cardiac rupture in a toddler - Peep Talving; Mari-Liis Ilmoja; Günter Taal; Karl-Gunnar Isand; Sandra Teppo; Erast-Henri Noor; Rein Kruusat; Andrus Remmelgas; Sten Saar (Elsevier, 2016)
Blunt cardiac rupture is typically a fatal injury with overall mortality exceeding 90%. Most of the patients never reach the hospital alive. In pediatric patients, only 0.03% of cases following blunt trauma admissions have a cardiac injury. This report presents a rare survivor of 16-months old toddler injured in a domestic accident suffering a right atrial rupture repaired through a median sternotomy. To the best of our knowledge this is the youngest case reported in the literature.